Rubbess
Rubbess
23-03-2020
Mathematics
contestada
Solve for x
4/3x^-1/3(x^2/3 -1)=0
Respuesta :
bamboola1
bamboola1
23-03-2020
Answer:
4/3 ^-1/3 (x^2/3 -1) = 1/3x^2/3 +1 1/3= 1 2/3+ 4/3^1 = 3^1 = 3
Step-by-step explanation:
Answer Link
VER TODAS LAS RESPUESTAS ( 52+ )
Otras preguntas
PLEASE HELP !!!!!! :)
2/n = 2/3a. n = 30c. n = 3b. n = 3/4d. n = 1 1/3
A compound microscope consists of an objective lens of focal length 2 cm and an eyepiece of focal length 6cm. if they are separated by a distance of 24cm, find
What is Fibroglandular density?
1000 800 Is Out DI. a) Atmospheric CO₂ A1B Atmospheric CO₂ (µatm) 600 400 A2 B1 B2 IS92 200 8.2 b) Global Ocean pH 8.1 8.0 7.9 7.8 7.7 160 c) Southern Ocean Sat
90 degree 15° 9.7 cm b cm (trignometric ratios)
When 13,000 units are produced, variable costs are $38 per unit and total costs are $624,000. what are the total costs when 15,000 units are produced?
If △WVX ~ △RTS, find x.
A spinner has 10 equally sized sections, 4 of which are green and 6 of which are red. the spinner is spun and, at the same time, a fair coin is tossed. what is
What is the net price after discount?